1997
DOI: 10.1046/j.1525-1497.1997.07110.x
|View full text |Cite
|
Sign up to set email alerts
|

Utilization and dosing of angiotensin-converting enzyme inhibitors for heart failure

Abstract: To determine if physician specialty is associated with underutilization and underdosing of angiotensin-converting enzyme inhibitors among patients with heart failure, we reviewed the charts of 214 outpatients with decreased systolic function at an urban academic medical center. Regardless of whether patients were cared for by cardiologists, generalist physicians, or a combination of the two specialties, approximately 75% of the patients were taking an angiotensinconverting enzyme inhibitor. However, only appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
0
1

Year Published

1997
1997
2009
2009

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(41 citation statements)
references
References 16 publications
1
39
0
1
Order By: Relevance
“…Also, few investigators have attempted to determine physician and patient factors associated with underutilization, 13,15 and whether underdosing occurs. 16 Therefore, we surveyed physicians about their knowledge of ACE inhibitors to explore whether underutilization of these medications persists. We aimed to determine whether patterns of self-reported use of ACE inhibitors vary by specialty type and other attitudinal, cognitive, and demographic attributes of the physicians, as well as by indication for the medication and the severity of the patient's illness.…”
mentioning
confidence: 99%
“…Also, few investigators have attempted to determine physician and patient factors associated with underutilization, 13,15 and whether underdosing occurs. 16 Therefore, we surveyed physicians about their knowledge of ACE inhibitors to explore whether underutilization of these medications persists. We aimed to determine whether patterns of self-reported use of ACE inhibitors vary by specialty type and other attitudinal, cognitive, and demographic attributes of the physicians, as well as by indication for the medication and the severity of the patient's illness.…”
mentioning
confidence: 99%
“…Systematic review has identified that trials of programs currently do not detail sufficiently what "usual" or "routine" care comparison groups received (20,22,25,26). This lack of detail creates bias because pharmacological care for HF varies widely over place, time, and sector (27,28). Prescription rates of key pharmacotherapies have differed historically and are influenced by geographic location (28), the availability of specialists (29,30), and the aggressiveness of management (31,32).…”
Section: Evidence From Current Trialsmentioning
confidence: 99%
“…This lack of detail creates bias because pharmacological care for HF varies widely over place, time, and sector (27,28). Prescription rates of key pharmacotherapies have differed historically and are influenced by geographic location (28), the availability of specialists (29,30), and the aggressiveness of management (31,32). These differences are crucial because any apparent effect (or lack thereof) in a trial could be attributed equally to variations in usual care as to the intervention (7).…”
Section: Evidence From Current Trialsmentioning
confidence: 99%
“…However, on chart review of patients with congestive heart failure at one academic medical center, only three quarters of eligible patients were taking an angiotensin-converting enzyme inhibitor, and only 60% of these were at doses known to be efficacious. 24 Then, in a recent survey, Jancin 25 found that cardiologists reported greater adherence than generalists to the 1994 Agency for Health Care Policy and Research guidelines for the treatment of congestive heart failure.…”
Section: Cardiac Diseasesmentioning
confidence: 99%
“…Deficiencies have been documented for the care of hypertension (recognition and treatment), 87,88 atrial fibrillation (knowledge regarding anticoagulation guidelines), 38 congestive heart failure (use of angiotensinconverting enzyme inhibitors), 24 hyperlipidemia (recognition and treatment), [89][90][91] and myocardial infarction (use of aspirin, thrombolytics, and ␤-blockers).…”
Section: Deficiencies In Management Of Diseasementioning
confidence: 99%